Sensory evaluation of organic and conventional fruits and vegetables available to Irish consumers. (11th September 2012) - Tobin, Rachel; Moane, Siobhan; Larkin, Tracey
Summary Many Irish consumers believe organic foods taste better; however, scientific data to support this are scarce, inconclusive and limited in scope. Quantitative descriptive analysis was used to compare the sensory properties of nine organic and conventional fruits and vegetables. A panel of nine was trained according to ISO international standards (8586‐1, 1993). Independent t‐tests of individual descriptor data and a two‐way repeated measures anova of the entire data set were carried out via SPSS 19. Statistical analysis of panel scores failed to show any significant differences between the organic and conventional samples for any of the descriptors assessed (P < 0.05 and less) or between the overall organic and conventional data sets (P < 0.05). In conclusion, the study found no statistically significant differences between the sensory attributes of a range of organic and conventional fruits and vegetables available to the Irish consumer.